Penggunaan Magnet Permanen Pada Prototipe Generator Linier - Raharjo, M. Didik, Hasyim Asy'ari, ST.MT (2016)
To reduce dependence on fossil energy sources, development of renewable energy need to be developed. One potential source of renewable energy in Indonesia is the energy of ocean waves. Having a vast sea area, as well as sea conditions Indonesia which has a sea wave height is a great potential in the development of renewable energy sources. Efforts to convert ocean wave energy into electrical energy is with a permanent magnet linear generator. This will certainly be one of the new opportunities to meet the electricity needs in every area, especially near waters with high waves. This study will discuss the design of a prototype generator windings linear and analyze the effect on the output of the linear generator. This linear generator using a rotor mounted five pairs of permanent magnet type ferrite and 6 slot stator frame with a number of turns from 400, 500 and 800. The linear generator generates the lowest voltage of 4.5 V at a speed of 100rpm winding 400 and the highest voltage 17, 9 v the number of turns 800 with a speed of 300 rpm. Data obtained from experiments conducted with lab scale can certainly be developed on a larger scale to be able to vary the types of magnets used, number of turns, up to the speed used to generate greater power.